Navigating Constructive Feedback in Indonesia’s PPG Practicum: Challenges, Emotions, and Emerging Feedback Literacy - Nadrun Nadrun; Mashuri Mashuri; Nur Sehang Thamrin; Abdul Kamaruddin (Universitas Lambung Mangkurat, 2026)
Constructive feedback is a core component of professional learning in school-based teaching practicums, yet pre-service teachers often experience difficulty turning feedback into concrete instructional improvement. This study aims to explore how pre-service teachers in the Indonesian Pendidikan Profesi Guru (PPG) program receive, interpret, and enact constructive feedback during the school-based teaching practicum (Praktik Pengalaman Lapangan/PPL), including the challenges they face and the strategies they use to respond. The study employed a qualitative phenomenological design. Participants included eight student teachers and five mentor teachers from seven partner schools in Palu, Indonesia. Data were collected through individual semi-structured interviews conducted in Indonesian, audio-recorded, transcribed verbatim, and analyzed using inductive thematic analysis. The findings show that student teachers generally accepted feedback as supportive and developmental, but enactment remained limited. Key barriers included pedagogical-technical difficulties (translating curriculum learning outcomes into ABCD-structured learning objectives, selecting appropriate instructional models, and aligning assessment practices), classroom enactment constraints (pacing, engagement, classroom management), affective pressures (low confidence, pressure from repeated revisions, confusion due to multiple inputs), and mentoring continuity issues (limited access to mentors/supervisors and delayed clarification). Despite these barriers, student teachers developed adaptive strategies, such as note-taking, iterative revision, peer collaboration, intensive consultation, and the use of digital and AI-supported resources, while mentor teachers supported progress through gradual coaching and combined verbal and written feedback. In conclusion, feedback effectiveness in PPL depends not only on student teachers’ positive acceptance but also on the acceptance-to-enactment pathway enabled by actionable feedforward, psychologically safe interactions, and sustained dialogic mentoring. The study implies that PPG programs should strengthen mentoring coordination, provide clear exemplars and criteria, and embed structured feedback literacy support to help pre-service teachers translate feedback into observable teaching improvement.